Predictors of having naloxone in urban and rural Oregon findings from NHBS and the OR-HOPE study. (1st October 2021) - Lipira, Lauren; Leichtling, Gillian; Cook, Ryan R.; Leahy, Judith M.; Orellana, E. Roberto; Korthuis, P. Todd; Menza, Timothy W.
Highlights: Not enough people who inject drugs and use opioids in Oregon have naloxone. Naloxone ownership may be more common in urban Oregon than rural Oregon. People who use meth, are homeless, and males may be less likely to have naloxone. Distribution via syringe service programs and pharmacies may improve access. Abstract: Purpose: Naloxone is an opioid antagonist that can be effectively administered by bystanders to prevent overdose. We determined the proportion of people who had naloxone and identified predictors of naloxone ownership among two samples of people who inject drugs (PWID) who use opioids in Portland and rural Western Oregon. Basic procedures: We used data from participants in Portland's National HIV Behavioral Surveillance (NHBS, N = 477) and the Oregon HIV/Hepatitis and Opioid Prevention and Engagement Study (OR-HOPE, N = 133). For each sample, we determined the proportion of participants who had naloxone and estimated unadjusted and adjusted relative risk of having naloxone associated with participant characteristics. Main findings: Sixty one percent of NHBS and 30 % of OR-HOPE participants had naloxone. In adjusted analysis, having naloxone was associated with female gender, injecting goofballs (compared to heroin alone), housing stability, and overdose training in the urban NHBS sample, and having naloxone was associated with drug of choice, frequency of injection, and race in the rural OR-HOPE sample. In both samples, having naloxone was crudely associated with SSP use, but this was attenuated after adjustment. Principal conclusions: Naloxone ownership was insufficient and highly variable among two samples of PWID who use opioids in Oregon. People who use methamphetamine, males, and people experiencing homelessness may be at increased risk for not having naloxone and SSP may play a key role in improving access.